(3GdYOI aj GdCUhds - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s ((3eMeO Hf OQhjT YhV GdMdjs)
(3ChdgG (B:s
(3HYO GdHSedI(B: (3GdMeO ddg QH GdYGdejf(B... (3SCdJe CjOce Gddg EedGA eNJUQ aj CUhd Gdabg jMjW HLejY CHhGHg Ydi SHjd GdEjLGR(B... (3aUd aj eGgjI CUhd Gdabg(B...s
(3BNQgG (B:s
(3Ef cGf eQGO GdbGFd HCfg dG Odjd Ydjg Cf Gdfaj bO cGf MGUdG ef bHd adjZdH Ydi GdXf HbGDg EPG de jXf eG jRjd Pdc GdXfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B84s
(3GdPQjYI HQbe(B: 1488s
(3EjVGM Gdecfhf(B: (3L(B2(3, U(B95s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs